Comprehensive genome characterization of solitary fibrous tumors using high‐resolution array‐based comparative genomic hybridization. Issue 2 (17th October 2012) - Bertucci, François; Bouvier‐Labit, Corinne; Finetti, Pascal; Adélaïde, José; Metellus, Philippe; Mokhtari, Karima; Decouvelaere, Anne‐Valérie; Miquel, Catherine; Jouvet, Anne; Figarella‐Branger, Dominique; Pedeutour, Florence; Chaffanet, Max; et al.
Abstract: Solitary fibrous tumors (SFTs) are rare spindle cell tumors with limited therapeutic options. Their molecular basis is poorly known. No consistent cytogenetic abnormality has been reported. We used high‐resolution whole‐genome array‐based comparative genomic hybridization (Agilent 244K oligonucleotide chips) to profile 47 samples, meningeal in >75% of cases. Few copy number aberrations (CNAs) were observed. Sixty‐eight percent of samples did not show any gene CNA after exclusion of probes located in regions with referenced copy number variation (CNV). Only low‐level CNAs were observed. The genomic profiles were very homogeneous among samples. No molecular class was revealed by clustering of DNA copy numbers. All cases displayed a "simplex" profile. No recurrent CNA was identified. Imbalances occurring in >20%, such as the gain of 8p11.23–11.22 region, contained known CNVs. The 13q14.11–13q31.1 region (lost in 4% of cases) was the largest altered region and contained the lowest percentage of genes with referenced CNVs. A total of 425 genes without CNV showed copy number transition in at least one sample, but only but only 1 in at least 10% of samples. The genomic profiles of meningeal and extra‐meningeal cases did not show any differences. © 2012 Wiley Periodicals, Inc.